Properties of Thermal Staircases Off the Northeast Coast of South America, Spring and Fall 1985 - Boyd, Janice D. (1989)
The staircase phenomenon is characterized by a vertical temperature, salinity, and density structure in which 5- to 50-m-thick well-mixed consecutive layers are separated by several-meter-thick interfaces across which temperature, salinity, and density change rapidly. In spring and fall 1985, AXBT surveys of a large area off the northeast coast of South America revealed an extensive field of subthermocline thermal staircases which is probably the site of vigorous salt fingering. During both seasons the staircases were shallowest in the south (180- 360 m) and deepest in th northwest (420-650 m), occurring on the average between the 8 and 13 C isotherms. Typically, each staircase consisted of 10 well-mixed layers with average thickness of 16 m and average interlayer temperature change of 0.52 deg. Thicker layers seemed to be associated with larger temperature changes. No seasonal variation in these parameters was observed. The interfaces separating the layers had a modal thickness of 2 m, with interfaces in the spring tending to be thinner than in the fall. The region bounded by 10 deg - 14 deg N, 52 deg - 57 deg W tended to have staircases with more layers, thicker layers, and larger interlayer temperature changes. The sharp northeastern staircase field boundary occurs at the confluence of the Subtropical Underwater and the Antarctic Intermediate Water, suggesting that the staircases may be formed in this region and then extend south and west to form the rest of the field. Pub. in Jnl. of Geophysical Research, v94 nC6 p8303-8312, 15 Jun 1989.